Great diverse rhizobial community nodulating Astragalus mongholicus in the northeastern region of China - Gao, Mengzhe; Yuan, Xiaoxia; Ji, Zhaojun; Yang, Bingjie; Li, Hua; Zhang, Bo (Frontiers in Microbiology, 2024)
IntroductionAstragalus mongholicus Bunge is an important medicinal legume species widely cultivated in northeastern China (NEC) and northwestern China (NWC) and can establish a symbiotic relationship with nitrogen-fixing rhizobial strains. However, there are limited reports comparing the genetic diversity, differentiation, and gene flow of rhizobial strains associated with this plant in different geographic regions.MethodsWe used multilocus sequence analysis (MLSA) to investigate the phylogeny and genetic diversity of rhizobia and to estimate their intra- and inter-regional gene flow and genetic differentiation based on the analysis of concatenated core genes (recA, atpD, and glnII) and the critical symbiotic gene nodC.ResultsWe isolated eight known and three novel genospecies representing four genera, among which Rhizobium yanglingense was the most predominant microsymbiont. Phylogenetic analysis revealed a highly diverse rhizobial community nodulating Astragalus mongholicus in NEC, consisting of the four genera Rhizobium, Bradyrhizobium, Sinorhizobium, and Mesorhizobium. This community differed markedly from the rhizobial community found in NWC. Various rhizobial genospecies with different symbiotic gene nodC sequences were capable of nodulating A. mongholicus in NEC. Therefore, A. mongholicus exhibits promiscuity in its association with symbionts in the natural environment, showing no strong preference for either the species-defining core genes or the symbiotic genes of rhizobia. We also found that the Glyco_tranf_GTA_type superfamily (Glycosyltransferase family A) is the most highly conserved and essential domain in the NodC protein, which is encoded by the symbiotic nodC gene, across nodulating rhizobia. In addition, we found independent genetic differentiation among rhizobial communities geographically, and the frequency of gene flow among microsymbionts between NEC and NWC was low. We speculate that the formation of the highly diverse rhizobial community in NEC resulted from the independent evolution of each ancestral lineage. This diversity likely arose from intraregional genetic differentiation driven by mutations rather than recombination.ConclusionEcogeographical isolation between NEC and NWC restricted inter-regional genetic drift and gene flow. Therefore, intraregional genetic differentiation is the major evolutionary force underlying the genetic diversity of rhizobia.